Obtenção e caracterização de lignina kraft utilizando resíduos industriais - Lima, Érickson Alex de (2022)
The objective of this work was to obtain and characterize Kraft lignin from the black liquor of a pulp and paper industry. First, the collection of lignin was carried out and later the physicochemical characterizations of the same were made. After these analyzes of the black liquor, acid precipitation was carried out with recycled (ARA) and analytical standard acid (APA), to then obtain Kraft lignin. The characterization of the lignin samples was composed by performing analyzes of spectroscopy in the infrared region with Fourier transform (FTIR), Scanning Electron Microscopy (SEM) with Energy Dispersive Spectroscopy (EDS), X ray Diffraction (DRX), Dynamic Light Scattering (DLS) and Zeta potential. With the results of the characterization it was possible to analyze the main properties of the obtained lignins. SEM analyzes showed irregular structures with different formats, such as plates and spherical structures. The elemental chemical analysis showed that the samples are similar to the results found in the literature for Eucalyptus grandis. With the results of XRD it was possible to determine the phases present in the structure of the samples. Regarding the DLS, it was possible to observe that there is a variation in the average sizes throughout the filtration and centrifugation process, due to the agglutination process of these samples in the phase separation process, and with Zeta potential it was possible to observe that the values obtained are similar to those found in other studies. The FTIR analysis showed characteristics of the chemical bonds of Kraft lignin, indicating that it was possible to obtain this. The data obtained were analyzed using the Tukey Test, which indicated that the best lignin yield occurs at pH 2, when APA was used yields of 30.51±0.0024% and 29.71±0.0054% for the ARA, results within the standards of the literature, as it is a Eucalyptus grandis and which show that the use of recyclable acid is feasible for the process.